Pengembangan Kesenian Tari Tradisional Sumatra Barat Dalam Perspektif Hak Kekayaan Intelektual (HKI) - Dr. Drs. I Nyoman Lodra.MS.i (Universitas PGRI Adi Buana Surabaya, 2015)
For many centuries. the domain of Traditional arts in West Sumatra has been untouched by the academics having creative power to access, analyze, criticize and even to create something on value novelty.